Ethical Formation in Professional, Scientific and Technological Education - Vinícius Bozzano Nunes; Leonardo Lemos de Souza (Universidade Federal do Rio Grande do Sul, 2018)
The mismatch between technological development and human development is evident in the Federal Network of Professional, Scientific and Technological Education, making ethical formation an important point of discussion in this context. This article shows results of research that investigates how this education is represented in the speech of the pedagogical managers of the Network. From the data, the emphasis is on disciplinary approaches and professional or professionalizing representations of business and neoliberal ethics. It is concluded that the morality theme should integrate the debates about Professional Education, reconciling the technical and human dimensions of formation and thus guiding the educational process toward emancipatory.